Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1365-3156.2012.03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital‐based surveillance for Lassa fever in Edo State, Nigeria, 2005–2008

Abstract: Abstractobjectives To estimate the burden of Lassa fever in northern and central Edo, a state in south Nigeria where Lassa fever has been reported.methods Blood samples were obtained from 60 patients hospitalised at the Irrua Specialist Teaching Hospital (ISTH), Irrua, with a clinical suspicion of Lassa fever and from 451 febrile outpatients seen at the ISTH and hospitals in Ekpoma, Iruekpen, Uromi, Auchi and Igarra. All samples were tested retrospectively by Lassa virus-specific RT-PCR. Outpatients were addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 9 publications
5
45
1
Order By: Relevance
“…Our results are very similar to the study by Ehichioya et al that found fever, abdominal pain, headache and sore throat to be present in more than 40% of patients (18). Nevertheless, fever was recorded in 100% of their cohorts whereas we found 73% in our cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are very similar to the study by Ehichioya et al that found fever, abdominal pain, headache and sore throat to be present in more than 40% of patients (18). Nevertheless, fever was recorded in 100% of their cohorts whereas we found 73% in our cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…Irrua is the headquarters of Esan-Central Local Government Area (LGA), Edo State, one of the local government areas with the highest prevalence of LVD in Nigeria [32]. The Research and Ethics Committee of ISTH approved the study, and written informed consent was obtained from the parents/guardians of the children involved in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In Edo State, Nigeria, where the rodent reservoir is endemic [7], Lassa fever is an important disease of public health concern, and outbreaks occur yearly [4, 8, 9]. …”
Section: Introductionmentioning
confidence: 99%